Association between circulating 25‐hydroxyvitamin D metabolites and periodontitis: Results from the NHANES 2009–2012 and Mendelian randomization study. (31st October 2022) - Li, Wenjing; Zheng, Qiwen; Xu, Mingming; Zeng, Changqing; Deng, Xuliang
Abstract: Aim: This study sought to investigate associations of 25‐hydroxyvitamin D (25(OH)D) metabolites with periodontitis and to assess causality using Mendelian randomization (MR). Materials and Methods: This study included 7246 participants of the National Health and Nutrition Examination Survey, 2009–2012. The association of periodontitis with 25(OH)D metabolites was assessed using multivariable logistic regression analysis. Two‐sample MR for 25(OH)D, 25(OH)D3, and C3‐epi‐25(OH)D3 with periodontitis ( n = 17, 353 cases/28, 210 controls) was conducted. The principal analysis employed the inverse‐variance‐weighted (IVW) approach. We controlled for horizontal pleiotropy using five additional methods. Results: Based on the observational study, each 1‐point increase in standard deviation of 25(OH)D lowered the risk of periodontitis by 15% (OR = 0.85, 95% confidence interval [CI]: 0.78–0.93, p = .006) after multivariable adjustment. A similar relationship was observed between 25(OH)D3 and periodontitis (OR = 0.88, 95% CI: 0.80–0.97, p = .031). Furthermore, a potential non‐linear association was found between periodontitis and both 25(OH)D and 25(OH)D3 . However, C3‐epi‐25(OH)D3 was not found to be associated with periodontitis risk. IVW‐MR showed that periodontitis risk was not significantly associated with genetically increased levels of 25(OH)D (OR = 1.02, 95% CI: 0.90–1.16, p = .732), 25(OH)D3 (OR = 1.04, 95% CI: 0.93–1.17, p = .472), or C3‐epi‐25(OH)D3 (OR = 1.11, 95% CI: 0.87–1.41, p = .400). The pleiotropy‐robust MR approaches yielded similar results after we had eliminated the variants with horizontal pleiotropy risk. Conclusions: Cross‐sectional observational analysis identified significant relationships between periodontitis with 25(OH)D metabolites, while findings based on MR study did not support a causal role.